Evaluation of the effects of Artemisia Annua L. and Moringa Oleifera Lam. on CD4 count and viral load among PLWH on ART at Mbarara Regional Referral Hospital: a double-blind randomized controlled clinical trial - Twinomujuni, Silvano S; Atukunda, Esther C; Mukonzo, Jackson K; Nicholas, Musinguzi; Roelofsen, Felicitas; Ogwang, Patrick E (BioMed Central Ltd, 2024)
BACKGROUND Initiation of ART among people living with HIV (PLWH) having a CD4 count ≤ 350cells/µl, produces poor immunological recovery, putting them at a high risk of opportunistic infections. To mitigate this, PLWH on ART in Uganda frequently use herbal remedies like Artemisia annua and Moringa oleifera, but their clinical benefits and potential antiretroviral (ARV) interactions remain unknown. This study examined the impact of A. annua and M. oleifera on CD4 count, viral load, and potential ARV interactions among PLWH on ART at an HIV clinic in Uganda. METHODS 282 HIV-positive participants on antiretroviral therapy (ART) with a CD4 count ≤ 350cells/µl were randomized in a double-blind clinical trial to receive daily, in addition to their routine standard of care either; 1) A. annua leaf powder, 2) A. annua plus M. oleifera, and 3) routine standard of care only. Change in the CD4 count at 12 months was our primary outcome. Secondary outcomes included changes in viral load, complete blood count, and ARV plasma levels. Participants were followed up for a year and outcomes were measured at baseline, 6 and 12 months. RESULTS. At 12 months of patient follow-up, in addition to standard of care, administration of A. annua + M. oleifera resulted in an absolute mean CD4 increment of 105.06 cells/µl, (p < 0.001), while administration of A. annua plus routine standard of care registered an absolute mean CD4 increment of 60.84 cells/µl, (p = 0.001) compared to the control group. The A. annua plus M. oleifera treatment significantly reduced viral load (p = 0.022) and increased platelet count (p = 0.025) and white blood cell counts (p = 0.003) compared to standard care alone, with no significant difference in ARV plasma levels across the groups. CONCLUSION A combination of A. annua and M. oleifera leaf powders taken once a day together with the routine standard of care produced a significant increase in CD4 count, WBCs, platelets, and viral load suppression among individuals on ART. A. annua and M. oleifera have potential to offer an affordable alternative remedy for managing HIV infection, particularly in low-resource communities lacking ART access. TRIAL REGISTRATION ClinicalTrials.gov NCT03366922.
Keywords: Artemisia annua, Moringa oleifera, Immunological recovery, CD4 count, Viral load, ART